Outcomes of percutaneous coronary intervention in patients with chronic total occlusion (CTO): a single-center study evaluating a new dedicated CTO program in Egypt - Hany Tawfik Fathelbab; Mahmoud Abdelghany; Michael Megaly; Mohamed Ashraf Shawky; Khaled Zeineldin (Egyptian Journal of Critical Care Medicine)
Abstract Purpose The conundrum of limited resources in developing countries leads to the abonnement and underutilization of percutaneous coronary intervention for chronic total occlusion, in addition to lack of expertise, limited supplies, and success rates. We embraced this challenge by initiating a dedicated program in a tertiary academic center in Egypt, aiming for optimum utilization of resources, limit cost, and gaining experience. We present our outcomes and the proficiency in establishing the program. Methods We enrolled all patients undergoing percutaneous coronary intervention for chronic total occlusion during the first year of initiating our dedicated program. Analysis of clinical data, angiographic findings, and procedural features were evaluated, aiming to evaluate outcomes. Our primary outcome was successful recanalization achievement, utilization of available resources and cost. Secondary outcomes such as peri-procedural myocardial infarction, coronary perforation, urgent need of coronary artery bypass grafting, cerebrovascular stroke, and mortality were assessed. Results Our study enrolled 64 patients electively admitted to the Critical Care Department, Cairo University, undergoing percutaneous coronary intervention for chronic total occlusion. The median J-CTO score was 2 (0–5). We achieved successful recanalization in 47 patients (73%). The mean procedural time was 123 ± 48.8 min, mean contrast volume was 359.03 ± 151.9 ml, and mean radiation dose was 9.4 ± 4.2 Gy. The mean number of wires per patient was 2.69 ± 1.32, and the most successful crossing strategy was antegrade wiring (56.3%). The commonest cause of failure was failure of re-entry (46.7%). One patient had peri-procedural MI (1.6%), and one patient required urgent CABG. There was no in-hospital mortality or cerebrovascular stroke. The cost ranged from 6520 Egyptian Pounds (EP) ($415) to 63,720 EP ($4058), with a mean of 26,213 EP ($1670). Conclusions Establishing a dedicated program for percutaneous coronary intervention for chronic total occlusion proved to be feasible and proficient, achieving high success rates with limited complications in view of limited resources, rationalized utilization of equipment, and limitation of hospital costs.